Faktor Faktor Memengaruhi Praktik Penghindaran Pajak (Sektor Pertambangan Tahun 2019-2021) - Rasya, Astrid Putri Adila; Ratnawati, Juli (LPPM Universitas BSI, 2023)
This research was conducted to examine thin capitalization, profitability, company size, and leverage as variables that influence tax avoidance practices. The population of this research is the mining sector which is listed on BEI in period of 2019-2021. Using a purposive sampling method, this research is having 33 sample from mining sector company. This research was using a secondary data that researcher obtained from BEI and financial report of every company that suited with purposive sampling criteria. Hypothesis testing uses multiple linear regression analysis with the help of SPSS software. The results showed that the independent variables thin capitalization and profitability have a negative effect on tax avoidance practices. otherwise, for size of company and leverage have a positive effect on tax avoidance act. Keyword: Leverage, Penghindaran Pajak, Profitabilitas, Ukuran Perusahaan, Thin Capitalization